Industrial Conflict in Developed and Developing Countries: Extending a Western Strike Model - Segalla, Michaël (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1995)
This paper tests a macroeconomic strike model widely used to study the incidence of labour conflict in developed countries on data from the world-at-large. Previous investigations of the influence of labour demand and worker wage expectations on strike frequency have produced contradictory results. Perhaps one reason for this is that these studies have left out all but the most developed countries and have rarely been comparative. This study uses a data set that includes data for 41 countries (approximately half of which are considered developing) from 1953-1985.